PENGARUH LITERASI DAN PENGELOLAAN KEUANGAN TERHADAP PENDAPATAN PADA UMKM DI LANGOWAN - Mamesah, Isaura Abigail; Lambut, Adventinus K (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2025)
This research aims to examine the impact of financial literacy and financial management on the income of MSMEs in Langowan. The study employs a descriptive design with a quantitative approach. The population comprises 2,100 MSME participants in Langowan. Convenience sampling was used as the sampling method, applying Hair et al.'s formula, which yielded a sample size of 120 respondents. Informasiwere collected through a questionnaire developed to assess financial literacy and financial management using a Likert scale, distributed via a Google Form link. Multiple linear regression analysis was performed using SPSS version 25. The partial analysis findings reveal that (1) financial literacy significantly influences income, (2) financial management significantly affects income, and (3) both financial literacy and financial management jointly have a significant impact on income.